Forest Policy Formulation : a Need to Review - Singh, Jarnail (Indian Forester, 1999)
The National Forest Policy represents long-term wishes of the nation in term of well-set objectives. It also provides a course to achieve the objectives in the form of a weU-defined strategy. The process of national forest policy formulation is, indeed, rich with over a hundred years old history. Over the years, we have three national policies, viz. National Forest Policy 1894, National Forest Policy 1952 and National Forest Policy 1988. Each policy is a comprehensive document of noble objectives and innovative strategies yet on the implementation front, the results are not very encouraging. This article examines the present policy formulation approach and points out inadequacies and gaps which are the probable causes of poor implementation. It outlines a holistic and natural strategy of policy formulation that provides for missing links in the present approach. The proposed strategy is inherently democratic, professional and transparent. It provides for mechanism to ensure implementation in a given time frame.